1989
DOI: 10.1159/000168014
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Proteinase Activity in Isolated Glomeruli of Streptozotocin Diabetic Rats

Abstract: The important initiating process of diabetic nephropathy is the glomerular accumulation of proteins which has been proposed to be due to a synergistic interaction of the disturbed intrarenal hemodynamic and the altered chemical composition of glomerular components. This study was performed to investigate whether there might be a reduced activity of glomerular proteinases in streptozotocin diabetic rats. Three weeks after the induction of diabetes by means of streptozotocin, we found a decreased proteinase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

1989
1989
2002
2002

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 12 publications
1
20
1
2
Order By: Relevance
“…Alterations in cathepsin activity were described in 1983 by Mohanam and Bose [16]. Teschner et al [17] subsequently found decreased glomerular proteinase (azocaseinase) activity in this model. Since metalloproteinases have no activity against azocasein, it is likely that cathepsin activity was being measured in this study.…”
Section: Discussionmentioning
confidence: 56%
“…Alterations in cathepsin activity were described in 1983 by Mohanam and Bose [16]. Teschner et al [17] subsequently found decreased glomerular proteinase (azocaseinase) activity in this model. Since metalloproteinases have no activity against azocasein, it is likely that cathepsin activity was being measured in this study.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, several investigators have examined MMP activity in diabetic models. Reckelhoff et al [30]described decreased glomerular metalloproteinase and Teschner et al [31]found decreased glomerular proteinase activity in diabetic rats. Nakamura et al [32]demonstrated diminishing levels of MMP-3 with age in glomeruli of streptozotocin-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…There is much evidence to suggest that the renal degradation of filtered proteins occurs in the lysosomes of the proximal tubules and lysosomal activity and/or trafficking to the lysosomes has been shown to decrease with the progression of experimental diabetes [5][6][7][35][36][37][38]. A reduction in the lysosomal activity/trafficking would account for the reduction in the degradation of IgG and transferrin, and the apparent increase in FC by RIA, with no increase in the glomerular sieving.…”
Section: Discussionmentioning
confidence: 99%